The Effectiveness of Government Public Relation in COVID-19 Era - Muhammad Rheza Ramdhan (Privietlab, 2021)
The main goal of this study is to discover public opinion on public policy in the year after COVID-19 and how the public relations effort that was successful was achieved by the government. Using Drone Emprit Academic's publicly available data, this research analyzes the public sentiment using naive bayes. This study based on 3,609 tweets of the term “kebijakan publik” showed that the majority of public opinion is unfavorable, and accounts in the civil sector are the most active. The government's positive news may be overshadowed by other sources, making it a problem. The government should work with the public relations department to craft a strategy to raise the volume of social media use and to counteract bad news with good news.